The Adventure zone. [4] : the crystal kingdom - McElroy, Clint, 1955-; Pietsch, Carey (First Second, 2021)
"A desperate call for help interrupts holiday celebrations at the Bureau of Balance, and sends Taako, Magnus and Merle on a high-stakes mission to find and reclaim a fourth deadly relic: a powerful transmutation stone, hidden somewhere in the depths of a floating arcane laboratory that's home to the Doctors Maureen and Lucas Miller. An unknown menace has seized control of the stone, and is using it to transform the lab into a virulent pink crystal that spreads to everything it touches. It's only a matter of time before this sparkling disaster crash-lands, but in order to find the stone and save the whole planet from being King Midased, our heroes will have to fight their way through a gauntlet of rowdy robots and crystal golems, decide whether they can trust the evasive Lucas Miller, and solve the mystery of what--or who--has put them all in peril, before there's no world left to save"--